Peran Orang Tua dalam Pendidikan Seks Bagi Remaja di Tengger Kandangan Surabaya - Sari, Intan Nurmalita; Yusuf, Ali (Jurusan Pendidikan Luar Sekolah Fakultas Ilmu Pendidikan UNESA, 2024)
This research aims to examine and analyze the role of parents in providing sex education for teenagers in Tengger Kandangan Surabaya, the inhibiting and supporting factors. The approach used in this research is descriptive qualitative. Data collection techniques include participatory observation, in-depth interviews and documentation with informants. The results of this research show that all parents play their role in providing sex education to teenagers, as evidenced by the way they provide sex education to teenagers by implementing boundaries for both the same and opposite sex and providing an approach that will create openness between the two. One of the supporting factors for parents providing sex education is that communication between them goes well and teenagers care about themselves.